2021
DOI: 10.1101/2021.07.23.453470
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PDZ-containing proteins targeted by the ACE2 receptor

Abstract: Angiotensin converting enzyme 2 (ACE2) is a main receptor for SARS-CoV-2 entry to the host cell. Indeed, the first step in viral entry is the binding of the viral trimeric spike protein to ACE2. Abundantly present in human epithelial cells of many organs, ACE2 is also expressed in the human brain. ACE2 is a type I membrane protein with an extracellular N-terminal peptidase domain and a C-terminal collectrin-like domain that ends with a single transmembrane helix and an intracellular 44-residues segment. This C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
1
1
Order By: Relevance
“…1 C ). Although it is a little weaker than the binding affinity measured by two recent experiments ( K D ≈ 3 and 5 μM, respectively) ( 32 , 37 ), our ITC result is in the normal range of canonical PBM/PDZ interaction (1 μM to 100 μM) ( 19 , 38 41 ). Based on previous knowledge, the positions P 3 and P 5 in the PBM should be acidic residues forming an acidic clamp interacting with the conserved residue Arg58 in the PDZ domain of SNX27 and especially the acidic residue at position P -3 is essential for the binding ( 38 ).…”
Section: Resultscontrasting
confidence: 81%
See 1 more Smart Citation
“…1 C ). Although it is a little weaker than the binding affinity measured by two recent experiments ( K D ≈ 3 and 5 μM, respectively) ( 32 , 37 ), our ITC result is in the normal range of canonical PBM/PDZ interaction (1 μM to 100 μM) ( 19 , 38 41 ). Based on previous knowledge, the positions P 3 and P 5 in the PBM should be acidic residues forming an acidic clamp interacting with the conserved residue Arg58 in the PDZ domain of SNX27 and especially the acidic residue at position P -3 is essential for the binding ( 38 ).…”
Section: Resultscontrasting
confidence: 81%
“…Biochemical and Crystallographic Characterization of Interaction between ACE2 and SNX27. During the preparation of our paper, several studies reported the existence of PBM in the C terminus of ACE2 (30,32,36), and it could bind to pairs of PDZcontaining proteins, among which SNX27 is the strongest binder for ACE2/PBM (32,37). Actually, sequence alignment of ACE2 from mammals shows PBM of ACE2 is well conserved and belongs to type I PBM (S/T-X-Ø, where X denotes any residue, and Ø denotes hydrophobic residue) (Fig.…”
Section: Resultsmentioning
confidence: 99%